Plano de negócio para a implantação de uma empresa internacional de e-commerce voltada à moda feminina - Mazetto, Rozana (My University, 2020)
This study had the objective to develop a business plan for the implementation of an international e-commerce company focused on women's fashion in England. To this end, specific objectives were established. The method used involved applied, qualitative, exploratory and descriptive research. The data were collected through bibliographic and documentary research, and a questionnaire was applied to three e-commerce specialists in the fashion industry, seeking to understand how the processes happening of buying and selling products through importation happen, in addition to seeking cost information, means, values, partners and how is this relationship in the international market, especially in England. Data analysis was performed using the Canvas. The method used involved applied, qualitative, exploratory and descriptive research. Data were collected through bibliographic and documentary research, and a questionnaire was applied to three e-commerce specialists in the fashion industry, seeking to understand how the processes of buying and selling products through importation happen, in addition to seeking cost information, means, values, partners and how is this relationship in the international market, especially in England. Data analysis was performed using the Canvas Model construction application for the case under analysis. The results showed that the enterprise is viable, but it is pointed out that the purchase of goods for inventory is a time-consuming process that can take months between placing the order and receiving the goods, given this fact, it is necessary that the entrepreneur has good capacity to organize the flow of purchases / inventory. At the same time, the e-commerce proposal seeks to reach a very specific audience and leaving the traditional, the success of the competitor "CyberDog" (party clothing store with neon colors and very striking) as a trend that was embraced by the English. At the same time, the entire process of creating and developing Canvas was considered a realistic expectation and a bet based on minimum values, with regard to costs, orders, expected revenue and others. In this way, it can be expected that e-commerce may emerge as a new way of shopping for English women, exceeding the realistic expectations proposed here. [resumo fornecido pelo autor]
Este estudo objetivou elaborar um plano de negócio para a implantação de uma empresa internacional de e-commerce voltada à moda feminina na Inglaterra. Para tanto, foram estabelecidos objetivos específicos. O método utilizado envolveu pesquisa aplicada, qualitativa, exploratória e descritiva. Os dados foram coletados mediante pesquisa bibliográfica e documental, e aplicação de questionário para três especialistas em e-commerce do ramo da moda, buscando entender como acontecem os processos de compra e venda de produtos por meio de importação, além de buscar informações de custos, meios, valores, parceiros e como é este relacionamento no mercado internacional, especialmente na Inglaterra. A análise de dados foi realizada por meio da aplicação construção do Modelo Canvas para o caso em análise. Os resultados demonstraram que o empreendimento é viável, mas aponta-se que a compra de mercadorias para estoque é um processo demorado que pode levar meses entre realizar o pedido e receber as mercadorias, diante deste fato, é preciso que o empreendedor tenha boa capacidade para organizar o fluxo de compras/estoque. Ao mesmo tempo, a proposta do e-commerce busca atingir um público bem específico e saindo do tradicional, aponta-se o sucesso da concorrente ?CyberDog? (loja de roupas de festa com cores neon e bem chamativas) como uma tendência que foi abraçada pelos ingleses. Ao mesmo tempo, todo o processo de criação e desenvolvimento do Canvas considerou-se uma expectativa realista e uma aposta partindo-se de valores mínimos, no que diz respeito aos custos, pedidos, expectativa de receita e outros. Deste modo, pode-se esperar que o e-commerce poderá despontar como uma nova forma de comprar pelas mulheres inglesas, superando as expectativas realistas aqui propostas. [resumo fornecido pelo autor]
Keywords: Comércio internacional; Comércio eletrônico; Moda - Comercialização; Negócios